ENHANCING LOCAL INNOVATION : THE ROLE OF MSMES IN BUILDING GLOBAL ECONOMIC RESILIENCE - Abdul Hafid; Rafiuddin Rafiuddin; Dinah Husniah (JURNAL PROFIT, 2025)
This study aims to examine the role of Micro, Small, and Medium Enterprises (MSMEs) in improving the local economy in Madawau Village, Madapangga District, Bima Regency. MSMEs are one of the sectors that have a major contribution to national and local economic growth, especially in creating jobs, increasing community income, and encouraging village economic independence. The research approach used is qualitative with a phenomenological design, through in-depth interviews and observations of MSME actors and the local community. The results of the study show that MSMEs in Madawau Village are able to increase community income by 20-30% per year, create jobs, and encourage innovation and creativity in the village community. However, the development of MSMEs in this village still faces challenges both internally, such as limited capital, skills, and business management, and externally, such as market competition and access to financing. Therefore, support is needed from the government, financial institutions, and community participation in strengthening the MSME ecosystem so that it can become a driving force for a sustainable local economy.